Planejamentos combinatórios construindo sistemas triplos de steiner - Barbosa, Enio Perez Rodrigues (2011)
Intuitively, the basic idea of Design Theory consists of a way to select subsets, also called blocks, of a finite set, so that some properties are satisfied. The more general case are the blocks designs. A PBD is an ordered pair (S;B), where S is a finite set of symbols, and B is a collection of subsets of S called blocks, such that each pair of distinct elements of S occur together in exactly one block of B. A Steiner Triple System is a particular case of a PBD, where every block has size only 3, being called triples. The main focus is in building technology systems. By resolvability is discussed as a Steiner Triple Systems is resolvable, and when it is not resolvable. This theory has several applications, eg, embeddings and even problems related to computational complexity.